The awareness of glass ceiling issue among women employees: a case study in Interscience Sdn. Bhd. / Morney Baya & Sylvia Amaya-Lyn Lindang - Baya, Morney; Lindang, Sylvia Amaya-Lyn (2007)
The topic of our study is “The Awareness of Glass Ceiling Issue among Women Employees: A Case Study in Interscience Sdn. Bhd”. Glass Ceiling was actually used to describe the discrimination that leads to barrier in hindering the advancement of promotion to upper level management among women. The term glass ceiling resembles the transparency of workflow which limits persons outside the dominant group in developing their career. The main objective of our study is in order to ensure the level of awareness among the women employees, to determine the barriers of career advancement and to determine the influence of job position and length of services on the level of awareness. In the method, our research design is cross sectional survey. Therefore individual are the unit of analysis. The sample size is 145 women employees in that organization. As for the sampling technique, simple random sampling and quota sampling is selected. In order to collect our data, we are using email questionnaire and personally administered questionnaires. As for the data analysis, we are using two types of test. First objective and second objective are using mean and standard deviation test in order to determine the level of each variable. The other test that was used is two-way ANOVA in order to test the third objective. The test was regarding the significant result of both variables. For the main findings based on the first objective, the levels of awareness among the women employees are average. With the second objectives, most of the career barrier stated in the questionnaires are said to be a minor obstacle for them in advancing the career. For the final objective, both of the independent variables are not significant whereby neither job position nor length of services significantly influence the level of awareness. As a conclusion, the levels of awareness among women employees are average in that organization.